Wykorzystanie mechanizmów protokołu z Kioto do rozwoju współpracy krajów rozwiniętych z krajami Azji Wschodniej, na przykładzie Chin i Japonii - Ciechelska, Agnieszka; Graczyk, Andrzej (The Use of Kyoto Protocol Mechanisms for Developing Co-Operation between Industrialized Countries and East Asian Countries on the Example of China and Japan, 2008)
Countries with commitments under the Kyoto Protocol agreed to introduce three market-based mechanisms: • Emissions Trading, • The Clean Development Mechanism (CDM), • Joint Implementation (JI). Those mechanisms stimulate development through technology transfer and investments. In the context of international co-operation, CDM and JI are the most important mechanisms. CDM and JI help countries with Kyoto commitments to meet their targets by reducing emissions carbon in other countries in a cost-effective efforts. Moreover, private sector and developing countries are encouraged to contribute to emission reduction. JI involves investments in emission reducing realized by industrialized countries in other developed countries. CDM is similar mechanism but investments are realized by industrialized countries in developing countries. The Kyoto Protocol and its mechanisms can be chance for Poland to participate in new possibilities of international co-operation. JI can create new investment sources in Poland. Japan can mainly be interested in a such solution in the context of emission allowances insufficiency. However, CDM project can be attractive for Poland as it presents possibilities for creating new investment markets. Especially China seems to have the potential to become a place for investments in alternative energy projects. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 48-59